4 - La politique rizicole de l’administration coloniale en Côte d’Ivoire (1898-1959) - Gouédan Richard Meignan; Tschiwily Bérenger Goly (Afrika Zamani, 2022)
Among the foodstuffs traditionnally cultivated by the Ivorian population, rice has a particular attention from the French colonialists and to a small extent maize. In fact, concerning the economic context dominated by the exploitation of natural products and the promotion of benefits cultures, rice has interested the colonial administration. Some strategies like supervision, constraint and motivation are used to lead the farmers to create and produce rice in biggest dimensions. This policy with various aspects, which aim to produce more local rice has not given expected results. In such a way, during the colonial period, in spite of the increase of local production of rice, we can also notice that the importation of rice towards Côte d’Ivoire remained constant.